Amblyopia and Real-World Visuomotor Tasks - Grant, Simon; Moseley, Merrick J. (Strabismus, 2011)
A question of increasing interest to the basic science and clinical management communities during the past decade is whether children and adults with amblyopia and associated binocular visual abnormalities experience difficulties in executing real-world actions, to which vision normally makes an important functional contribution. Here we provide objective evidence that they do, by reviewing quantitative data from a number of studies comparing their performance with that of matched normally sighted subjects on a range of everyday visuomotor tasks. Because in real life, these tasks (grasping objects, walking, driving, reading) are habitually performed with both eyes open, our focus is on their binocular skill deficits, rather than those with their amblyopic eye alone. General findings are that individuals with abnormal binocularity show impairments in critical aspects of motor control-movement speed, accuracy or both-on every one of these activities, the extent of which correlates with their loss of stereoacuity, but not the severity of their amblyopia. Impairments were especially marked when the task was time-limited or novel. Implications are that children and adults with severely reduced or absent binocularity may be accident-prone when required to respond rapidly to unexpected situations and that amblyopia management should focus more attention on evaluating and restoring stereoacuity and stereomotion processing.